2006
DOI: 10.1108/09685220610717772
|View full text |Cite
|
Sign up to set email alerts
|

A modular approach to ERP system selection

Abstract: Purpose -This paper aims to study an enterprise resource planning (ERP) software selection problem. The primary goal of this paper is to propose a two-phase procedure to select an ERP vendor and a suitable ERP software. Design/methodology/approach -In the first phase of the proposed method the preliminary actions -such as constructing a project team, collecting all possible information about ERP vendors and systems, and identifying the ERP system characteristics -are established. In the second phase, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Apart from general ERP selection criteria (such as, system functionality, technical capacity, vendor support and fee, and industrial reputation) that are well reported in the literature [e.g. 12,13,14], the interview findings suggest that an additional set of cloud-specific requirements will need to be taken into analysis, such as location of data storage, data protection standard and practice, legal restrictions, and cloud service quality and availability.…”
Section: Further Discussion and Recommendationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Apart from general ERP selection criteria (such as, system functionality, technical capacity, vendor support and fee, and industrial reputation) that are well reported in the literature [e.g. 12,13,14], the interview findings suggest that an additional set of cloud-specific requirements will need to be taken into analysis, such as location of data storage, data protection standard and practice, legal restrictions, and cloud service quality and availability.…”
Section: Further Discussion and Recommendationsmentioning
confidence: 96%
“…9, 10, 11], ERP selection criteria [e.g. 12,13,14], ERP critical success factors [e.g. 15,16], and risks and barriers affecting ERP implementation and post-implementation [e.g.…”
Section: Brief Review Of Existing Erp and Cloud Literaturementioning
confidence: 99%
“…• [26] presentan una metodología basada en dos pasos: identificación de las propiedades de sistemas ERP existentes, y el uso de un modelo matemático para minimizar el costo de contratación e integración. • [27]…”
Section: Metodologías Para La Selección De Sistemas Erpunclassified
“…After defuzzification of fuzzy evaluations (intelligence, functional and non-functional requirements, the importance and relationship of the systems pairwise for integration issues), and after the gathering of the quantitative data about implementation costs and times, the data are converted into a parameterised format for the multi-objective model. To design this model, the authors took ideas from Sen et al (2009) and Ziaee et al (2006) and added extensions to their works. In this model, six objectives that compete with each other are considered.…”
Section: Design and Solve The Multi-objective Programming Modelmentioning
confidence: 99%